Evaluating the efficacy and safety of tumor treating fields versus laser interstitial thermal therapy in glioblastoma treatment: a comprehensive systematic review and meta-analysis - Emhemed, Marwa SaedAli; Murhega, Roméo Bujiriri; Stanley, Asogwa Chukwuebuka; Mugenyi, Nathan; Ayantayo, Temitayo; Mustapha, Mubarak Jolayemi; Adrien, Tangmi Djabo Eric; Dossou, Mèhomè Wilfried; Ibekwe, Jonas Lotanna; Bankole, Nourou Dine Adeniran; Kyaruzi, Victor Meza (Journal of Surgical Protocols and Research Methodologies, 2023)
Tumor Treating Field (TTF) is considered a new treatment option for glioblastoma. Studies in newly diagnosed GBM (ndGBM) patients have demonstrated a good safety profile and improved efficacy. On the other hand, Laser Interstitial Thermal Therapy (LITT) is a minimally invasive method for treating intracranial tumors that are challenging to treat using conventional techniques.LaserInterstitial Thermal Therapy,a minimally invasive method,is the most indicated treatment technique.Its safety and effectiveness,however,have not been thoroughly substantiated in the literature. To create an accurate understanding of which therapy yields better outcomes to glioblastoma patients regarding safety and efficacy, we decided to run a systematic review and meta-analysis on their comparative safety and therapeutic effects in the treatment of glioblastoma.We used standard and extensive Cochrane search methods.The latest search date was June 2nd, 2023. The study period goes from inception to date. We included Randomized Controlled Trials (RCT) or quasi-RCT and all human-based observational studies assessing the comparative safety and therapeutic outcomes of tumor treating fields to laser interstitial thermal therapy in treating glioblastoma patients.We did not include case reports,abstract-only titles,letters to the editor, conference proceedings, articles with missing data, articles in other languages, and those reporting animal studies. Our study compares Tumor Treating Fields’ safety and therapeutic effects on Laser Interstitial Thermal therapy in treating glioblastoma
Keywords: Tumor Treating Field; Glioblastoma; Diagnosis